Effects of UVC irradiation and thermal treatment on the physico-chemical properties and microbial reduction of clear and turbid tamarind juice - Mohd Hanif, H. A.; Shamsudin, Rosnah; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Tamarind juice is commonly treated with thermal treatment to inactivate microorganisms. However, thermal treatment deteriorates the appearance and flavor of tamarind juice. In this study, the performance of UVC treatment on clear and turbid tamarind juice as an alternative to thermal treatment was investigated. Results showed that UVC treatment was able to reduce E. coli O157:H7 by 7-log reduction but unable to completely remove the total bacterial population as observed in thermally treated clear and turbid tamarind juices. The pH of treated tamarind juices was comparable to each other. Nonetheless, UVC treatment caused significant changes on the flavor of the juice as it significantly reduced the total soluble solids of tamarind juices and decreased the titratable acidity of turbid tamarind juice. However, UVC treatments retained the appearance i.e. turbidity and color of tamarind juices better than thermal treatment.